English Pronunciation Practices: From Tongue Twisters to YouTube Channel - Vivi Aulia (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Background: Pronunciation plays an important role to create effective communication since incorrect pronunciation may lead to misunderstanding. The EFL teachers should be aware of this issue by identifying the appropriate methods for teaching pronunciation to EFL students, with expectations; students may correctly pronounce the English words that support comprehensible communication. This research aims at describing the tongue twisters method for practicing English pronunciation as well as the YouTube channel for sharing their pronunciation practices.Methodology: This research employed an observation sheet and pronunciation task through students’ tongue twisters video uploaded on the YouTube channel as the instruments. The observation sheet was applied to find out students’ activities of tongue twisters practice in five meetings and their difficulties during the practice. Meanwhile, students’ uploaded tongue twisters video on the YouTube channel was analyzed to get the result of their tongue twisters practice.Findings: The students were given 26 tongue twisters consisting of 24 English consonant sounds to pronounce four times for each of them. The result showed that tongue twisters for sounds /p/, /f/, /v/, /ð/, and /z/ were difficult enough for them due to the interference of their mother tongue that commonly missed on these sounds. Besides that, the highest percentage of students who got a score of 60-69 on their YouTube channel video indicates that they still need more practice.Conclusion: Having tongue twisters’ practice and uploading the practice video on YouTube channel create learning experiences for students. They need to allocate more time practicing the English pronunciation better intensively. Therefore, the teachers should create maximal lesson planning and preparation to make sure that each student gets the same opportunity to practice it.